Contemporary Approaches for Aneurysm Repair - Mosley, Mary (MD Conference Express, 2013)
Aortic aneurysms are the 12th leading cause of death in Western societies—a silent but deadly disease, often with no symptoms until they rupture. This article reviews the natural history, indications, and approaches for endovascular and open aortic aneurysm repair in both the abdomen and the thorax.